Coscinaraea marshae corals that have survived prolonged bleaching exhibit signs of increased heterotrophic feeding - Bessell-Browne, P.; Stat, Michael; Thomson, D.; Clode, P. (Springer Verlag, 2014)
Colonies of Coscinaraea marshae corals from Rottnest Island, Western Australia have survived for more than 11 months in various bleached states following a severe heating event in the austral summer of 2011. These colonies are situated in a high-latitude, mesophotic environment, which has made their long-term survival of particular interest as such environments typically suffer from minimal thermal pressures. We have investigated corals that remain unbleached, moderately bleached, or severely bleached to better understand potential survival mechanisms utilised in response to thermal stress. Specifically, Symbiodinium (algal symbiont) density and genotype, chlorophyll-a concentrations, and δ13C and δ15N levels were compared between colonies in the three bleaching categories. Severely bleached colonies housed significantly fewer Symbiodinium cells (p < 0.05) and significantly reduced chlorophyll-a concentrations (p < 0.05), compared with unbleached colonies. Novel Symbiodinium clade associations were observed for this coral in both severely and moderately bleached colonies, with clade C and a mixed clade population detected. In unbleached colonies, only clade B was observed. Levels of δ15N indicate that severely bleached colonies are utilising heterotrophic feeding mechanisms to aid survival whilst bleached. Collectively, these results suggest that these C. marshae colonies can survive with low symbiont and chlorophyll densities, in response to prolonged thermal stress and extended bleaching, and increase heterotrophic feeding levels sufficiently to meet energy demands, thus enabling some colonies to survive and recover over long time frames. This is significant as it suggests that corals in mesophotic and high-latitude environments may possess considerable plasticity and an ability to tolerate and adapt to large environmental fluctuations, thereby improving their chances of survival as climate change impacts coral ecosystems worldwide.